(3OQGSI aj CKQ GdCReGJ GdUMjI hGdHjFjI aj EfJGL hJWhQ GdCacGQ GdSjGSjIs - (3CMeO cQje(B, (3UGdMs ((3YeGf(B;(3YeGf(B:s (3OGQ CeLO ddfTQ hGdJhRjY(B;(3EHUGQ fGTQhf h ehRYhf(B,s, 2023)
(3jbOe cJGH (B'(3GdCReGJ GdYGdejI hGdacQ GdSjGSj GdZQHj(B' (3JMdjdkG YejbkG dcjajI JTcjd GdCReGJ GdUMjI hGdHjFjI GdcHQi, eKd LGFMI chajO(B-19 (3hGdJZjQ GdefGNj, ddfbGTGJ GdSjGSjI GdeYGUQI aj GdZQH(B. (3ef NdGd OQGSI JWhQ GdCacGQ Mhd GdOhdI, hGdMhceI, hGdeSDhdjI GdaQOjI, hGdYOGdI GdGLJeGYjI aj CYbGH gPg GdCReGJ, jcTa GdcJGH Yf JMhdGJ LhgQjI aj GdJacjQ GdSjGSj GdZQHj(B. (3jSdW GdeDda GdVhA Ydi cjajI OaY gPg GdCReGJ UfGY GdbQGQ hGdehGWfjf Ydi EYGOI Jbjje GdChdhjGJ GdbhejI, hJWhjQ SjGSGJ LOjOI JhGLg GdJMOjGJ GdeYbOI GdJj JWQMgG gPg GdCReGJ GdeJTGHcI(B. (3GdcJGH jSGge HTcd cHjQ aj agefG dcjajI JTcjd GdCReGJ ddghjGJ GdSjGSjI, hEYGOI JTcjd GdYdGbGJ Hjf GdOhdI hGdeLJeY, hJMOjO eSGQ GdJWhQGJ GdSjGSjI GdeSJbHdjI aj GdZQH(B.s
(3GdeQGLY U(B.205s
Keywords: (3GdacQ GdSjGSj(B- (3GdCReGJ GdYGdejIs; (3GdfXQjGJ GdSjGSjI(B- (3GdCReGJ GdHjFjI hGdUMjIs